The Impact of Renewable Energy Policy Implementation on Green Economy Growth in Southeast Asia - Phương, Bích (Cebong Journal, 2025)
The Impact of Renewable Energy Policy Implementation on Green Economy Growth in Southeast Asia The rapid expansion of renewable energy has become a cornerstone of sustainable development strategies worldwide, particularly in regions striving to balance economic growth with environmental protection. This research examines the impact of renewable energy policy implementation on green economy growth in Southeast Asia, focusing on its role in promoting clean energy adoption, job creation, sustainable investment, and emissions reduction. A qualitative and comparative approach was employed, analyzing policy frameworks across selected Southeast Asian countries and evaluating their alignment with global best practices, such as those of the European Union, China, and India. The findings reveal a strong correlation between renewable energy adoption and key green economy indicators, with policies serving as critical drivers of energy security, decarbonization, and socio-economic resilience. However, the study also identifies significant policy gaps, including inconsistent regulatory frameworks, limited financing mechanisms, and uneven implementation among member states. Despite these challenges, regional cooperation through ASEAN initiatives and alignment with the United Nations Sustainable Development Goals have provided a foundation for collective progress. The research concludes that strengthening policy harmonization, expanding investment opportunities, and fostering cross-border energy cooperation are essential to accelerate the transition toward a low-carbon, inclusive, and sustainable economy in Southeast Asia.